ASSESSMENT OF WILDLIFE DISTRIBUTION IN RELATION TO WATERHOLES IN MARGUBA RANGE OF OLD OYO NATIONAL PARK, NIGERIA - Onihunwa, J. O.; Akande, Olalekan A.; Mohammed, H. L.; Joshua, D. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed wildlife distribution in relation to waterholes in Marguba range of Old Oyo National Park, Nigeria. It involved Observations, Identification and Counting of different wildlife species utilizing each of the waterholes in the Park. Data obtained was analyzed using descriptive statistics. Four (4) waterholes are recorded in the Park (Oopo River, Ogun River, Ayinta River and Ibuya River). The frequency distribution of herbivores species observed around the waterholes revealed that Ogun River recorded no herbivores. Also Kob recorded the highest number of observation with 7 individuals, follows by Roan antelope with 4 individuals while Red flanked Duiker, Waterbuck and Western hartebeest recorded 1 individual each. The frequency distribution of non-human primates species observed around the waterholes, Oopo and Ayinta River recorded no observation. Ibuya recorded the highest number with 4 individuals while Ogun recorded 2 individuals. The frequency distribution of amphibians/reptiles’ species observed around the waterholes, Ibuya recorded the highest number with 11 individuals, followed by Oopo River with 3 observations while Ogun and Ayinta recorded 1 individual each. Also Frog (Rana sp) recorded the highest with 7 individuals. The animal indices around the waterholes showed that herbivores recorded the highest with 48.35, followed by Amphibian/Reptile with 31.0% while Non-human primates is the least with 20.7%. The study recommends that provision of functional artificial waterholes in the park should be established.